2006
DOI: 10.1038/emm.2006.82
|View full text |Cite
|
Sign up to set email alerts
|

Association of common promoter polymorphisms of MCP1 with hepatitis B virus clearance

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant cancers closely associated with chronic infection by the hepatitis B virus (HBV) or the hepatitis C virus (HCV) throughout the world. In this study, the genetic associations of 20 known polymorphisms in eight candidate genes, including angiotensinogen (AGT), cadherin 1 (CDH1), cyclooxygenase 2 (COX2), monocyte chemotactic protein-1 (MCP1), multidrug resistance 1 (MDR1), chemokine ligand 5 (RANTES), thrombospondin 2 (THBS2), and thrombospondin 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 44 publications
(62 reference statements)
1
34
0
Order By: Relevance
“…3 In addition to that, several previous studies have also reported associations between genetic polymorphisms and the risk of HCC and/or clearance of HBV. [3][4][5][6][7] D-type cyclins are the main integral mediators associating the extracellular signaling environment with cell-cycle progression. They are divided into three subtypes: cyclin D1, D2 and D3.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition to that, several previous studies have also reported associations between genetic polymorphisms and the risk of HCC and/or clearance of HBV. [3][4][5][6][7] D-type cyclins are the main integral mediators associating the extracellular signaling environment with cell-cycle progression. They are divided into three subtypes: cyclin D1, D2 and D3.…”
Section: Introductionmentioning
confidence: 99%
“…All control individuals were in accordance with Hardy-Weinberg equilibrium. Two studies were of Caucasians [13,14]; the others were focused on Asians [11,12,[17][18][19][20]. However, two studies only presented the allelic data, our attempts of obtaining genotypic data from these two studies have failed.…”
Section: Resultsmentioning
confidence: 99%
“…Two of them were not performed in humans; seven studies were not focused on RANTES; four studies were vaccine related; eight were not casecontrol studies; one of them used the same dataset with a previous study; six studies did not analyze RANTES -403 polymorphism. According to our search strategy, eight case-control studies were eventually included in this meta-analysis [11][12][13][14][17][18][19][20]. Specific selection process is displayed in the flow chart in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also verified the correlation of RANTES gene polymorphisms with HBV infection. These studies have invariably found a lack of association between the RANTES gene and HBV infection (Duan et al, 2005;Ahn et al, 2006;Park et al, 2006;Cheong et al, 2007;Thio et al, 2008). Despite the increased prevalence of HBV infections in Saudi Arabia, no information is available regarding RANTES gene polymorphisms and their relationships with viral susceptibility and disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical course of HBV infection varies from spontaneous recovery after acute hepatitis to a chronic persistent infection that may progress to cirrhosis or HCC. The mechanisms underlying resolution of acute HBV infection or its progression to chronicity are not clearly understood but are suggested to depend on host immune response and genetic factors (Grakoui et al, 2003;Bowen and Walker, 2005;Park et al, 2006;Durantel and Zoulim, 2009).…”
Section: Introductionmentioning
confidence: 99%